Comparative Analysis of the Impact of Volleyball on Physical Fitness Improvement in Male and Female Students of the Communication Science Program at UPN Veteran Yogyakarta - Sumintarsih, Sumintarsih; Saptono, Tri; Mustofa, Hanafi (CV. Publikasi Indonesia, 2024)
Research objectives the effect of volleyball games on improving the physical fitness of male students. The effect of volleyball games on improving the physical fitness of female students. The difference in the effect of volleyball games between male and female students on improving physical fitness. This research an uses experimental method. The population of this research were students of the Communication Science Study Program of UPN